2014
DOI: 10.1371/journal.pone.0101276
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Bioactive Lipids from Composite Microgel-Microsphere Injectable Scaffolds Enhances Stem Cell Recruitment and Skeletal Repair

Abstract: In this study, a microgel composed of chitosan and inorganic phosphates was used to deliver poly(lactic-co-glycolic acid) (PLAGA) microspheres loaded with sphingolipid growth factor FTY720 to critical size cranial defects in Sprague Dawley rats. We show that sustained release of FTY720 from injected microspheres used alone or in combination with recombinant human bone morphogenic protein-2 (rhBMP2) improves defect vascularization and bone formation in the presence and absence of rhBMP2 as evaluated by quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Some studies have focused on the recruitment of MSCs to the bone defect site for treating the nonunions. Das et al [2014] showed that FTY720 (a small molecule) enhances MSC recruitment to the calvarial defect of rats, thus promoting skeletal repair. They suggested that sustained release of FTY720 from injected microspheres used alone or in combination with rhBMP-2 improves the recruitment of MSCs and subsequently increases bone repair.…”
Section: Msc Homing and Recruitment To Bone Defectsmentioning
confidence: 99%
“…Some studies have focused on the recruitment of MSCs to the bone defect site for treating the nonunions. Das et al [2014] showed that FTY720 (a small molecule) enhances MSC recruitment to the calvarial defect of rats, thus promoting skeletal repair. They suggested that sustained release of FTY720 from injected microspheres used alone or in combination with rhBMP-2 improves the recruitment of MSCs and subsequently increases bone repair.…”
Section: Msc Homing and Recruitment To Bone Defectsmentioning
confidence: 99%
“…We have shown previously that local administration of FTY720 regulates the trafficking of inflammatory and osteogenic progenitor cells to sites of injury [9, 10, 32]. In order to assess the phenotype of cells recruited to the graft region, we performed immunohistochemical staining on defect tissue sections to visualize macrophages (CD68) and stromal populations enriched for osteogenic progenitor cells (CD29, CD90) [32].…”
Section: Resultsmentioning
confidence: 99%
“…In order to assess the phenotype of cells recruited to the graft region, we performed immunohistochemical staining on defect tissue sections to visualize macrophages (CD68) and stromal populations enriched for osteogenic progenitor cells (CD29, CD90) [32]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because FTY720 affects both the recruitment and cytokine elaboration of MO [9], and because sustained release of FTY720 over several weeks can be achieved using PLGA microparticle carriers [17], we next attempted therapeutic immunomodulation using local delivery of FTY720-loaded PLGA microparticles (Figure 3a). To achieve sustained local delivery of FTY720 during the progression of immune cell infiltration, 50:50 PLGA microparticles encapsulating FTY720 (total dose encapsulated in microparticles = 10 μg, drug:polymer ratio = 1:150) were injected into supraspinatus muscle at the time of surgery.…”
Section: Resultsmentioning
confidence: 99%